The role of general surgery in consultations of pregnants from obstetrics and gynaecology department (Annals of Medical Research, 2021)
Aim: According to the current literature, the most common non-obstetric indications requiring surgery during pregnancy are appendicitis, biliary diseases, adnexal pathologies such as torsion or neoplasm, trauma, breast-related diseases and bowel obstruction. In this study, we sought to investigate the factors that may increase the risk for general surgery interventions in pregnants.Material and Methods: We reviewed of all cases of pregnants that consulted to general surgery in May 2012-July 2018. 74 pregnants were consulted to general surgery for various reasons. Of those patients, 41 (55.4%) of them required medical and surgical intervention, while 33 (44.6%) had conservative treatment. Patients were divided into two groups as general surgery intervention (GSI) and no need to medical and surgical intervention, just observation was enough (non-GSI).Results: The rate of urgent intervention (UI) was (9 out of 41) 22% in SI. Of the 9 pregnants, 8 (88.9%) had acute appendicitis. The other one is acute cholecystitis. The mean WBC was statistically higher in SI group than non-SI (13.568±3.892 vs 10.665±3.184, p=0.0008). Addition to this late pregnancies are more likely to be in GSI group.Conclusion: According to our study results, late periods of pregnancy may increase risk for requiring GSI in pregnants and UI, as well. Also elevated WBC values should alert the physician about general surgery intervention requirement.Keywords: Consultation; pregnant; surgery.
Keywords: Consultation; pregnant; surgery.